2017
DOI: 10.1084/jem.20171406
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s disease: A matter of blood–brain barrier dysfunction?

Abstract: Montagne et al. examine the role of blood–brain barrier (BBB) dysfunction in Alzheimer’s neurodegeneration and how targeting the BBB can influence the course of neurological disorder in transgenic models with human APP, PSEN1 and TAU mutations, APOE4 (major genetic risk), and pericyte degeneration causing loss of BBB integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
446
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 522 publications
(486 citation statements)
references
References 198 publications
(292 reference statements)
14
446
0
7
Order By: Relevance
“…By contrast, individuals homozygous for the most common allele, APOE*ε3, have a reduced risk of AD and show a decreased degree of BBB breakdown 147,152,156,158 . As reviewed elsewhere 11 , multiple experimental studies have confirmed that BBB breakdown causes capillary leakage in AD models of β-amyloidosis 159162 and in APOE*ε4 transgenic mice 71,163,164 .…”
Section: Postmortem Evidence Of Bbb Disruptionmentioning
confidence: 83%
See 3 more Smart Citations
“…By contrast, individuals homozygous for the most common allele, APOE*ε3, have a reduced risk of AD and show a decreased degree of BBB breakdown 147,152,156,158 . As reviewed elsewhere 11 , multiple experimental studies have confirmed that BBB breakdown causes capillary leakage in AD models of β-amyloidosis 159162 and in APOE*ε4 transgenic mice 71,163,164 .…”
Section: Postmortem Evidence Of Bbb Disruptionmentioning
confidence: 83%
“…Most mechanistic insights have been gained from animal models of these disorders 6,11 . However, the development of advanced neuroimaging techniques that are capable of interrogating changes in BBB integrity in humans in regions as small as hippocampal subfields 46,49,65,66 , and improved imaging techniques for determining regional cerebral blood flow and haemodynamic responses 2 , enlarged perivascular spaces 55 , and incidence and distribution of microbleeds, using high strength 7T magnets to increase the detectability of these vascular changes 87,104 , hold considerable promise for future neurovascular research in humans.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors have reported reduced expression of adhesion molecules and tight junction proteins in BBB endothelial cells combined with a dysfunctional and/or disrupted neurovascular unit in AD patients with early disease long before the occurrence of dementia and in the absence of neurodegeneration and brain atrophy [382][383][384]. Importantly, such damage may result from the presence of prolonged systemic inflammation and elevated levels of PICs, which increase the permeability of tight junctions by decreasing levels of glycocalyx and other adhesion molecules, as well as causing endothelial cell damage and disruption of the of glia limitans [385,386].…”
Section: The Function Of the Bbb In This Modelmentioning
confidence: 99%